2007
DOI: 10.1128/mcb.00218-07
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Regulatory Mechanism of the Bone Morphogenetic Protein (BMP) Signaling Pathway Involving the Carboxyl-Terminal Tail Domain of BMP Type II Receptor

Abstract: Bone morphogenetic proteins (BMPs) are members of the transforming growth factor ␤ (TGF␤) family of growth factors performing multiple essential functions in embryos and adult metazoans (19,20). The BMP receptors initiate a cascade of Ser/Thr phosphorylation upon binding of BMPs, starting with the BMP type II receptor (BMRPII) kinase phosphorylating and activating the BMPRI kinase, which phosphorylates and activates downstream signal transducers, the Smad proteins, and thus modulates gene expression (2,3,7,30,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
124
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 113 publications
(127 citation statements)
references
References 52 publications
(86 reference statements)
3
124
0
Order By: Relevance
“…In BMP-responsive osteoblasts, Trib3 is bound to the intracellular portion of the BMPRII receptor at the cell cortex and is released upon ligand binding. In the cytoplasm, Trib3 binds and degrades SMURF1, an E3 ubiquitin ligase specific for the BMP mediator Smad, effectively stabilizing Smads (Chan et al, 2007). In TGFb-responsive HepG2 cells, Trib3 binds the MH domain of Smad3, enters the nucleus, and acts as a co-factor to modulate target gene expression (Hua et al, 2011).…”
Section: Subcellular Localization Of Tribsmentioning
confidence: 99%
“…In BMP-responsive osteoblasts, Trib3 is bound to the intracellular portion of the BMPRII receptor at the cell cortex and is released upon ligand binding. In the cytoplasm, Trib3 binds and degrades SMURF1, an E3 ubiquitin ligase specific for the BMP mediator Smad, effectively stabilizing Smads (Chan et al, 2007). In TGFb-responsive HepG2 cells, Trib3 binds the MH domain of Smad3, enters the nucleus, and acts as a co-factor to modulate target gene expression (Hua et al, 2011).…”
Section: Subcellular Localization Of Tribsmentioning
confidence: 99%
“…Overexpression of the TGF-β activator (TARAM-A*) and the antagonist, Lefty1 confirmed that TGF-β signaling is required for trb3 expression in the embryos. Studies have shown that Trb3 physically interacts with the BMP type II receptor in mammalian cells and thereby regulates BMP signaling (Chan et al, 2007). BMPs and their receptors belong to the TGF-β super family and are critical for ventral patterning in vertebrates (von Bubnoff and Cho, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Over-expression of trb3 reduces level of smurf1 transcripts Studies in the pulmonary artery smooth muscle cells (PASMCs) show that TRB3 regulates Smurf1 in association with BMP signaling components (Chan et al, 2007). We thus examined the putative correlation between Smurf1 and Trb3 in zebrafish embryogenesis.…”
Section: Forced Expression Of Trb3 Ventralizes the Embryosmentioning
confidence: 99%
See 2 more Smart Citations